Cyp3A4 *1G polymorphism is associated with alcohol drinking: A 5-year retrospective single centered population-based study in China. - Xiaoqing Jia; Xiaoting Zhang; Tao Zhou; Dalong Sun; Rong Li; Na Yang; Zheng Luo (PLoS ONE)
Introduction We investigated the epidemiology of Cytochrome P450 (CYP) 3A4 genotype and the relationship between CYP3A4 genotype and alcohol drinking habits. Materials and methods A single-centered retrospective study was conducted on 630 patients who underwent CYP3A4*1G genetic testing. Their relevant information on epidemiology and etiology was collected. Laboratory testing, including CYP3A4*1G genotype, liver function tests, and serum lipid measurements were performed. Bi-variate logistic regressions were used to examine the relationship between variables. The relationship between alcohol drinking and CYP3A4*1G genotype was estimated. Demographic and clinical features were analyzed. Participants with drinking history were divided into non-heavy drinking and heavy drinking groups. Liver function and dyslipidemia of participants with drinking histories were compared between CYP3A4*1G mutation (GA+AA) and wild-type (GG) groups. Results Participants with CYP3A4*1G mutation(GA+AA) had an increased adjusted odds ratio (AOR) of 2.56 (95% CI, 1.4-4.65; P = 0.00) for alcohol abuse when compared with participants without CYP3A4 mutation (GG). In the subgroup of participants with alcohol abuse, there are no significant differences in liver injury levels and serum lipid levels between CYP3A4*1G mutant and wild-type groups. Patients with CYP3A4*1G mutation had an increased AOR of cardiac-vascular diseases and malignant diseases compared with patients without CYP3A4*1G mutation. The epidemiology had no difference between GA and AA group. Conclusion The study indicated that there was association between alcohol drinking and CYP3A4*1G genetic mutation. In the subgroup of participants with alcohol abuse, there are no significant differences in liver injury and dyslipidemia between CYP3A4*1G mutant and wild-type groups. CYP3A4*1G mutation was also related to cardiac-vascular diseases and malignant diseases.